4D characterisation of damage and fracture mechanisms of ultra high performance fibre reinforced concrete by in-situ micro X-Ray computed tomography tests. (February 2020) - Yang, Z.J.; Qsymah, A.; Peng, Y.Z.; Margetts, L.; Sharma, R.
Abstract: In-situ microscale X-ray computed tomography (μXCT) tests of ultra high performance fibre reinforced concrete (UHPFRC) specimens were conducted under progressive wedge-split loading for the first time. A sequence of μXCT images of two 40 × 20 × 25 mm notched specimens were obtained at different loads with a voxel resolution of 16.9 μm. Through 3D image processing, the UHPFRC's internal microstructures are characterised and the complicated damage and fracture mechanisms are visualised, including bridging, bending and pull-out of fibres, spalling and fracture of matrix, and evolution of micro-cracks into macro-cracks. The deformed μXCT images clearly show the significant effects of steel fibres: suppressing microcracks from propagation, leading to dispersed multiple cracks, and contributing to deviate the originally vertical crack towards the overall fibre orientation across the cracks. It is concluded the in-situ μXCT tests provide an unrivalled tool for elucidation of complicated damage and fracture evolution in UHPFRC with high-resolution 3D images that will be invaluable for validation of numerical models and optimisation of the material's micro-structures.